Jerzy Żuławski i jego działalność w Łodzi w październiku 1914 r. - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2015)
Jerzy Żuławski, who had been engaged in spreading the ideas of the legionaries, visited Lodz together with the representatives of the PNO Commiserate on 18th October 1914. His main tasks were to censor local newspaper and publish the „To the arms!” magazine, in which he addressed mainly the current events. The poet was also performing other activities aiming at promotion of the ideas of the Legions, among others, by trying to convince the local elites to his ideology – mainly in the form of private letters. Żuławski was one of the organizers and speakers during the rally in the Grand Theater. Even considering his significant attempts, the ideas spread among the citizens of Lodz were not successful. The poet left the city together with other PNO Commissioners on 28th October 1914. He died of typhoid few months later.